Migration, tied foreign aid and the welfare state - Panos Hatzipanayotou; Michael S. Michael (Center for Economic Studies and ifo Institute (CESifo), 2005)
In this paper we highlight aspects related to the links between international migration, foreign tied aid and the welfare state. We model migration as a costly movement from an aid-recipient developing country with low income, poor infrastructure, and no welfare system, towards a rich donor, developed country with a well-developed welfare system. Within this model we find, among other things, that the best response of the developed donor country is to increase aid as the co-financing rate by the recipient country increases. When the immigration cost decreases, e.g. due to greater economic integration between the two countries, it is beneficial for the donor country to increase aid.
Keywords: F22; H23; F35; 330; migration; tied foreign aid; welfare state; Internationale Wanderung; Entwicklungshilfekonditionen; Sozialstaat; Migrationstheorie; Zwei-Länder-Modell; Nord-Süd-Beziehungen; Theorie